Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1063/1.4940721
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the general thermal field equation for nanosized emitters

Abstract: During the previous decade, K.L. Jensen et. al. developed a general analytical model that successfully describes electron emission from metals both in the field and thermionic regimes, as well as in the transition region. In that development, the standard image corrected triangular potential barrier was used. This barrier model is valid only for planar surfaces and therefore cannot be used in general for modern nanometric emitters. In a recent publication the authors showed that the standard Fowler-Nordheim th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It has already been shown that the FN equation is valid only for surfaces with radii of curvature larger than ≈ 20 nm 31,32 . Although the behaviour of non-planar emitters has been studied extensively [33][34][35][36][37][38] , these works relied on analytical approximations for the surface potential barrier, the assumption of a smooth, well defined surface for the emitter and a semi-classical approach for the transmission probability.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that the FN equation is valid only for surfaces with radii of curvature larger than ≈ 20 nm 31,32 . Although the behaviour of non-planar emitters has been studied extensively [33][34][35][36][37][38] , these works relied on analytical approximations for the surface potential barrier, the assumption of a smooth, well defined surface for the emitter and a semi-classical approach for the transmission probability.…”
Section: Introductionmentioning
confidence: 99%
“…It is the assumptions on the shape of V (x) that limit the validity of the FN and GTF equations and in some cases, even their recent extensions of ref. [12,13]. In the standard theories based on the SN barrier, the electrostatic potential is approximated to be linear V (x) = F x where F is the local field at the emitting point.…”
Section: A Generalized Shape Of the Tunnelling Barriermentioning
confidence: 99%
“…The latter approximation is in principle valid only for planar surfaces, and practically valid for emitter radii of curvature R grater than 15-20nm. In the recent extensions of [12,13], a quadratic curvature-dependent term was added to the linear one, giving the form…”
Section: A Generalized Shape Of the Tunnelling Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Relying on the ever-increasing computing power, several numerical models have followed one another since the '80s. They brought insights into the heating evolution in time [28,29,30] along with more accurate considerations of the underlying quantum dynamics [31,32,33]. Concerning the contribution of the Nottingham effect to the emitter self-heating, modeling works have shown that it was predominant over the resistive heating at low current density, while the situation reverses at higher density [34,35].…”
Section: Introductionmentioning
confidence: 99%